PENGGUNAAN MEDIA PEMBELAJARAN ONLINE EDMODO UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN FISIKA MATERI MOMENTUM DAN IMPULS UNTUK SISWA KELAS X SMA NEGERI 3 MANDAU - Oktabella Regina; Fakhruddin Fakhruddin; Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the cognitive learning outcomes of students and find out the differences in cognitive learning outcomes of Class X students of SMA 3 Mandau using Edmodo online learning media and conventional learning on physics material momentum and impulses. The type of research used is quasi-experimental and research design is intact group comparison. The research subjects were class X students of SMA 3 Mandau Academic Year 2018/2019 which amounted to 72 students. The research data is learning outcomes data, consisting of post-test scores through the use of Edmodo online learning media. Data were analyzed descriptively and inferentially to see how students' learning outcomes improved after using Edmodo online learning media. The results of the analysis of the data obtained were, the absorption rate of the experimental class was higher than the absorption rate of the control class with the absorption score of the experimental class average of 81,66 and the absorption rate of the control class average 70,92. The effectiveness of learning refers to the average absorptive score of each class with an experimental class score of 81.66 belong to the effective category and the control class 70.92 belong to the effective category. Based on the hypothesis test carried out obtained a significance value (sig.2-tailed) 0.000 <0.05 so that it can be concluded that there are significant differences between the cognitive learning outcomes of students after using Edmodo online learning media and conventional learning.Key Words : Edmodo, Learning Outcomes, Momentum and Impulse.